Interpretation of Key Points in 2024 Chinese Expert Consensus on EGFR Exon 20 Insertion Mutations in Non-Small Cell Lung Cancer - Xuanhong JIN; Fei ZHOU (Zhongliu Fangzhi Yanjiu, 2025)
The Chinese Society of Clinical Oncology (CSCO) NSCLC Expert Committee has updated the 2023 Chinese expert consensus in light of the growing understanding of epidermal growth factor receptor (EGFR) exon 20 insertion (ex20ins) mutations in non-small cell lung cancer (NSCLC) and the emergence of new clinical data from targeted therapies. Based on the latest domestic and international literature, clinical evidence, and expert experience, the “Chinese Expert Consensus on the Standardized Diagnosis and Treatment of Non-Small Cell Lung Cancer with EGFR Exon 20 Insertion Mutations (2024 Edition)” introduces refinements in the diagnostic and upcoming therapeutic strategies for this rare mutation. This article also highlights the key updates and recommendations in the 2024 consensus compared to the 2023 version as well as outlines future directions to optimize clinical practices and improve patient outcomes.